Multispectral optoacoustic tomography (MSOT) for imaging the particle size-dependent intratumoral distribution of polymeric micelles - Cong ZQ (Dove Medical Press, 2018)
Zhaoqing Cong, Feifei Yang, Li Cao, Han Wen, Taotao Fu, Siqi Ma, Chunyu Liu, Lihui Quan, Yonghong Liao Key Laboratory of Bioactive Substances and Resources Utilization of Chinese Herbal Medicine, Institute of Medicinal Plant Development, Chinese Academy of Medical Sciences and Peking Union Medical College, Haidian District, Beijing 100193, People’s Republic of China Purpose: This study proposes the utilization of multispectral optoacoustic tomography (MSOT) to investigate the intratumoral distribution of polymeric micelles and effect of size on the biodistribution and antitumor efficacy (ATE). Materials and methods: Docetaxel and/or optoacoustic agent-loaded polymeric micelles (with diameters of 22, 48, and 124 nm) were prepared using amphiphilic block copolymers poly (ethylene glycol) methyl ether-block-poly (D,L lactide) (PEG2000–PDLLAx). Subcutaneous 4T1 tumor-bearing mice were monitored with MSOT imaging and IVIS® Spectrum in vivo live imaging after tail vein injection of micelles. The in vivo results and ex vivo confocal imaging results were then compared. Next, ATE of the three micelles was found and compared. Results: We found that MSOT imaging offers spatiotemporal and quantitative information on intratumoral distribution of micelles in living animals. All the polymeric micelles rapidly extravasated into tumor site after intravenous injection, but only the 22-nm micelle preferred to distribute into the inner tumor tissues, leading to a superior ATE than that of 48- and 124-nm micelles. Conclusion: This study demonstrated that MSOT is theranostically a powerful imaging modality, offering quantitative information on size-dependent spatiotemporal distribution patterns after the extravasation of nanomedicine from tumor blood vessels. Keywords: multispectral optoacoustic tomography, MSOT, polymeric micelle, in vivo imaging, intratumoral distribution, particle size, tumor model